2016
DOI: 10.1016/j.mechmat.2016.06.006
|View full text |Cite
|
Sign up to set email alerts
|

An elastoplastic damage model for fractured porous media

Abstract: a b s t r a c tAn elastoplastic damage model is developed for fractured porous media. The elastic-plastic response of stress-strain is captured by a bounding surface plasticity within the critical state framework, while the damage evolution due to hydro-mechanical effects is addressed using a continuum damage model that is distinguished from the existing models by accounting for the plastic hardening parameter, stress ratio, confining pressure and strain rate. The coupling between the elastic-plastic response … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 27 publications
1
24
0
Order By: Relevance
“…The framework solves fully coupled nonlinear partial differential equations for pressures, deformation and damage evolutions. We have shown that it is possible to combine Simo and Pister's (Simo and Pister, 1984) fracture methodology with Ma et al's (Ma et al, 2016). Ma et al's (Ma et al, 2016) double permeability model to produce a simple yet effective hydraulic fracture prediction tool, neither methodology interfering with the other coupled such that the model can replicate mutual interaction between fluid and porous domains and all associated behaviours within an elastic scenario.…”
Section: Discussionmentioning
confidence: 99%
“…The framework solves fully coupled nonlinear partial differential equations for pressures, deformation and damage evolutions. We have shown that it is possible to combine Simo and Pister's (Simo and Pister, 1984) fracture methodology with Ma et al's (Ma et al, 2016). Ma et al's (Ma et al, 2016) double permeability model to produce a simple yet effective hydraulic fracture prediction tool, neither methodology interfering with the other coupled such that the model can replicate mutual interaction between fluid and porous domains and all associated behaviours within an elastic scenario.…”
Section: Discussionmentioning
confidence: 99%
“…As the strain caused by damage does not contribute to the nominal stress, the constitutive equation of the welded bimrocks in any damage state should be as follows [38,39]:…”
Section: Damage Constitutive Modelmentioning
confidence: 99%
“…To obtain the damage evolution equation, it is necessary to establish the internal relation between the total strain and damage. Considering an arbitrary element of the bimrocks, the relation can be obtained according to the law of energy conservation [37][38][39], as follows:…”
Section: Damage Constitutive Modelmentioning
confidence: 99%
“…derived a cavity expansion solution for rock medium, to evaluate bear capacity of piles in rocks based on generalized Hoek‐Brown criteria. Unlike soils or sands, the behavior of rocks under loading is significantly affected by damage evolution, e.g., the development of microcracks, pore collapse and degradation of rock strength 37–49 . These defects normally have been treated as damage, and could be modeled by a damage scalar for isotropic conditions or a tensor for anisotropic conditions 37,43–44,50–58 .…”
Section: Introductionmentioning
confidence: 99%